A Case Study of Indonesian Frozen Shrimps Export Detention by FDA ( Food and Drug Administration) in 1998 - Wahidah, Efiyatul; Kadarisman, Darwin; Muhandri, Tjahja (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
Export detention cases of Indonesian fishery products to the United State in 1995 caused a financial lost up to US 17.580.738. Frozen shrimps, one of the top export commodities also experienced a detention case by FDA. Up until now frozen shrimps that are exported from Indonesia to the United State have been block listed by the government of the United State and have undergone an automatically detention and inspection procedure. The objective of this research was to determine the major problems of Indonesian frozen shrimps export detention cases by the FDA in 1998, and also determine the main factors that caused these problems in order to proceed with quality correction action. The results showed that the major problems of export detention cases of Indonesian frozen shrimps were Salmonella. The main factors causing Salmonella were quality of fresh shrimps, a not well design and application of HACCP system in the frozen shrimp industries, time and sensitivity of Salmonella assay methods. Quality correction actions can be applied at shrimp farms, frozen shrimps industries and the government Â Keywords: frozen shrimps, export detention